2016
DOI: 10.1038/srep34592
|View full text |Cite|
|
Sign up to set email alerts
|

Attenuation of Na/K-ATPase Mediated Oxidant Amplification with pNaKtide Ameliorates Experimental Uremic Cardiomyopathy

Abstract: We have previously reported that the sodium potassium adenosine triphosphatase (Na/K-ATPase) can effect the amplification of reactive oxygen species. In this study, we examined whether attenuation of oxidant stress by antagonism of Na/K-ATPase oxidant amplification might ameliorate experimental uremic cardiomyopathy induced by partial nephrectomy (PNx). PNx induced the development of cardiac morphological and biochemical changes consistent with human uremic cardiomyopathy. Both inhibition of Na/K-ATPase oxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(105 citation statements)
references
References 33 publications
2
103
0
Order By: Relevance
“…Recently, we have demonstrated that both manoeuvers activate Na/K-ATPase/c-Src signaling and cause carbonylation modification of proteins. Administration of pNaKtide (a peptide originated from a segment of the Na/K-ATPase α1 subunit, functioning as an antagonist of Na/K-ATPase/c-Src signaling), in both cases, blocks the signaling and carbonylation modification, as well as significantly attenuates the phenotype of uremic cardiomyopathy by partial nephrectomy and adipogenesis by a high fat diet [134,135]. …”
Section: The Role Of Ros In Na/k-atpase Signaling Mediated Rpt Sodmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have demonstrated that both manoeuvers activate Na/K-ATPase/c-Src signaling and cause carbonylation modification of proteins. Administration of pNaKtide (a peptide originated from a segment of the Na/K-ATPase α1 subunit, functioning as an antagonist of Na/K-ATPase/c-Src signaling), in both cases, blocks the signaling and carbonylation modification, as well as significantly attenuates the phenotype of uremic cardiomyopathy by partial nephrectomy and adipogenesis by a high fat diet [134,135]. …”
Section: The Role Of Ros In Na/k-atpase Signaling Mediated Rpt Sodmentioning
confidence: 99%
“…This might also be the case of chronic oxidative stress in which Na/K-ATPase signaling is insensitive to stimulation. By interrupting this amplification loop, pNaKtide antagonizes Na/K-ATPase signaling-mediated oxidant amplification and oxidative modification of Na/K-ATPase and other proteins, to relieve the overall oxidant stress to the physiological level that will restore the capability of CTS-mediated Na/K-ATPase signal transduction [134,135]. On the other hand, in clinic trials, antioxidant supplementation has been shown to be beneficial (such as combination antioxidant supplement containing zinc, ascorbic acid, α-tocopherol and β-carotene, as well as glutathione and vitamin C) [149,150,151], ineffective (such as a combination antioxidant supplement containing ascorbic acid, synthetic vitamin E and β-carotene) [152] or even dangerous [106,153,154].…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…The 5/6 th partial nephrectomy (PNx) animal models developed uremic cardiomyopathy phenotypes that were significantly attenuated by antagonizing CTS and Na/K-ATPase signaling [29, 7679]. When examining the possible role of the oxidant amplification loop in PNx-induced uremic cardiomyopathy, we observed that when the oxidant amplification loop was blocked with the synthetic peptide pNaKtide, and the development of phenotypical features of uremic cardiomyopathy was significantly attenuated [80]. The pNaKtide (which is membrane permeable by a TAT leading sequence) is derived from the ND1 segment (amino acid residues 379–435) of pig Na/K-ATPase α1 subunit N domain [50, 81].…”
Section: The Positive-feedback Amplification Loop and Experimental DImentioning
confidence: 99%
“…Administration of pNaKtide (7 days) at higher doses was able to reverse PNx-induced anemia and cardiac hypertrophy, as well as some echocardiographic features of uremic cardiomyopathy. In left ventricle homogenates, administration of pNaKtide at higher doses attenuated PNx stimulated Na/K- ATPase/c-Src signaling, protein carbonylation, and type I collagen expression [80]. …”
Section: The Positive-feedback Amplification Loop and Experimental DImentioning
confidence: 99%
“…We have demonstrated the involvement of these cardiac glycosides-specific receptor Na/K-ATPase and ROS amplification, in mediating the development of LV hypertrophy, cardiac cell apoptosis and fibrosis in the process of uremic cardiomyopathy [11,19,40,41]. For the remainder of this review, we will focus on the mechanisms by which this appears to occur.…”
Section: Pathophysiology Of Uremic Cardiomyopathymentioning
confidence: 99%